2007
DOI: 10.1007/s00423-007-0186-1
|View full text |Cite
|
Sign up to set email alerts
|

How to improve satisfaction with hospital stay of severely injured patients

Abstract: In the present study, the perceived quality of psychosocial care proved to have a significant effect on patients' satisfaction with their hospital stay. Results of the current analysis thus indicate that psychosocial aspects of physician-patient interaction are of considerable importance in the medical care of seriously injured patients. Although this study is mainly based on subjective patient reported outcome, there is evidence that the subjective view of a patient is relevant in many aspects of medical trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…Empirical studies have confirmed that a trusting physician-patient interaction promotes adherence to treatment (Nguyen et al 2009;Trachtenberg et al 2005), improved health outcomes (Berrios-Rivera et al 2006;Mollborn et al 2005;Safran et al 1998) and patient satisfaction (Hall et al 2002;Janssen et al 2007; Thom and Campbell 1997). Hence, trust seems to be a key component of the physician-patient interaction and consequently it appears relevant that physicians know how trust can be established and maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have confirmed that a trusting physician-patient interaction promotes adherence to treatment (Nguyen et al 2009;Trachtenberg et al 2005), improved health outcomes (Berrios-Rivera et al 2006;Mollborn et al 2005;Safran et al 1998) and patient satisfaction (Hall et al 2002;Janssen et al 2007; Thom and Campbell 1997). Hence, trust seems to be a key component of the physician-patient interaction and consequently it appears relevant that physicians know how trust can be established and maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Dissatisfaction is an adverse outcome of care, sometimes leading to long-lasting frustration for both patients and health care staff. Dissatisfaction is linked to distrust in the health care staff or system, 1 and patients who are discontent are less likely to comply with medical advice and medication. 2 Previous studies of possible determinants of stroke patient satisfaction/dissatisfaction have mainly focused on late phases after stroke.…”
mentioning
confidence: 99%
“…The study population did not differ significantly from the non-participants in regard to gender, age, degree of injury, time after discharge and length of hospital stay [13]. An overview of descriptive characteristics of all variables used in the following analysis is given in Table 1.…”
Section: Resultsmentioning
confidence: 98%
“…There is growing evidence that patient participation in medical treatment is important [13]. Participation in treatment can be measured with the concept of shared decision making [14].…”
Section: Introductionmentioning
confidence: 99%